2020
DOI: 10.1109/tmc.2019.2897561
|View full text |Cite
|
Sign up to set email alerts
|

Real-Time Crowd Monitoring Using Seamless Indoor-Outdoor Localization

Abstract: Human identification and monitoring are critical in many applications, such as surveillance, evacuation planning. Human identification and monitoring are not an easy task in the case of a large and densely populated crowd. However, none of the existing solutions consider seamless localization, identification, and tracking of the crowd for surveillance in both indoor and outdoor environments with significant accuracy. In this paper, we propose a novel and real-time surveillance system (named, SmartISS) which id… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(17 citation statements)
references
References 37 publications
0
13
0
Order By: Relevance
“…XMPP is an open and decentralized messaging protocol that allows exchanging messages between the clients regardless of the operating system [ 81 ]. Kulshrestha et al [ 96 ] used this protocol to provide reliable communication between the portable sensing units (PSU) and the XMPP server and vice versa in order to compute the top-k queries.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…XMPP is an open and decentralized messaging protocol that allows exchanging messages between the clients regardless of the operating system [ 81 ]. Kulshrestha et al [ 96 ] used this protocol to provide reliable communication between the portable sensing units (PSU) and the XMPP server and vice versa in order to compute the top-k queries.…”
Section: Resultsmentioning
confidence: 99%
“…This technology is based on cellular base-stations, which provide a long coverage area. Here, there are four standards used in the current studies 2G, 3G, 4G, and in last years 5G [ 74 , 96 , 108 ]. The improvements of each standard along the years permit to achieve better position estimation.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…This environment-centric application’s nature limits the applicability and widespread use in real-life scenarios. Hence, there is a dire need for environment-independent localization algorithms that are feasible for both indoor and outdoor applications [ 94 , 95 , 96 ]. This will eventually improve the adaptability of these applications in practical applications such as emergency evacuations, shipment/cargo tracking, and mission-critical applications.…”
Section: Future Directionsmentioning
confidence: 99%
“…• Safety and security: It has been shown that it is possible to monitor crowds using WiFi remote positioning and detect anomalous behavior through the use of outlier detection [77]. The authors developed an algorithm that finds differences from the normal behavior of a crowd and displays the last location of the individual having the anomalous behavior.…”
Section: Wifi Remote-positioning Use Cases 29mentioning
confidence: 99%